An investigation into the detection of seafloor massive sulphides through sonar - Mitchley, Michael (My University, 2012)
Sea oor massive sulphides are deep sea mineral deposits currently being examined as a potential mining resource. Locating these deposits, which occur at depths in the order of 2km, is currently performed by expensive submersible sonar platforms as conventional sonar bathymetry products gathered by sea surface platforms do not achieve adequate spatial resolution. This document examines the use of so-called high resolution beamforming methods (such as MUSIC and ESPRIT) for sonar bathymetry, together with combinations of parameter estimation techniques, including techniques for full rank covariance matrix estimation and signal enumeration. These methods are tested for bathymetric pro le accuracy using simulated data, and compared to conventional bathymetric methods. It was found that high resolution methods achieved greater bathymetric accuracy and higher resolution than conventional beamforming. These methods were also robust in the presence of unwanted persistent signals and low signal to noise ratios.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Submarine geology; Marine biology; Sea-floor spreading; Hydrothermal deposits